2018
DOI: 10.3390/cryst9010018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Segmental Orientational Order in a Smectic Mesophase of a Thermotropic Ionic Liquid Crystal

Abstract: We investigate conformational dynamics in the smectic A phase formed by the mesogenic ionic liquid 1-tetradecyl-3-methylimidazolium nitrate. Solid-state high-resolution 13C nuclear magnetic resonance (NMR) spectra are recorded in the sample with the mesophase director aligned in the magnetic field of the NMR spectrometer. The applied NMR method, proton encoded local field spectroscopy, delivers heteronuclear dipolar couplings of each 13C spin to its 1H neighbours. From the analysis of the dipolar couplings, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 32 publications
6
32
0
Order By: Relevance
“…This is in contrast to non-ionic smectics, which are prepared aligned either in intermediate nematic phase or by slow cooling from the isotropic state [24,47]. The sample alignment with the director distributed in the plane perpendicular to the magnetic field was confirmed by recording an 13 C NMR spectra [42]. The 1 H NMR spectra in the mesophase displayed a dipolar-broadened line of about 8 kHz wide and correspondingly short spin-spin relaxation time below 100 μs.…”
Section: Diffusion In a Smectic A Phase Of A Hydrated C 12 Mimclmentioning
confidence: 93%
See 1 more Smart Citation
“…This is in contrast to non-ionic smectics, which are prepared aligned either in intermediate nematic phase or by slow cooling from the isotropic state [24,47]. The sample alignment with the director distributed in the plane perpendicular to the magnetic field was confirmed by recording an 13 C NMR spectra [42]. The 1 H NMR spectra in the mesophase displayed a dipolar-broadened line of about 8 kHz wide and correspondingly short spin-spin relaxation time below 100 μs.…”
Section: Diffusion In a Smectic A Phase Of A Hydrated C 12 Mimclmentioning
confidence: 93%
“…This structure favours the formation of smectic phases induced by phase segregation of incompatible, charged and hydrophobic, moieties. Electrostatic cationanion interactions contribute to the stabilisation of layered structures, which can be formed with relatively low molecular orientational order as compared to that in their nonionic counterparts [41,42]. The most extensively studied ILCs are based on imidazolium cation.…”
Section: Smectic Layered Phasementioning
confidence: 99%
“…Additionally, the phase diagram in hydroscopic ILCs is affected by water-anion hydrogen bonding [1,6,9]. Theoretical and experimental studies of orientational order in ILCs [1,[10][11][12][13][14] revealed that, due to the contribution of the electrostatic interactions to the stabilization of layered structures, smectic phases in ILCs exhibit significantly lower value of the molecular orientational order parameter S as compared to that in its non-ionic counterparts. However, systematic studies of the orientational order parameter depending on ILCs structure and ionic composition are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these “mountain peak” grains with uniform grain size present an array distribution which reveals the orientation change of the perovskite grain growth and confirms the intensity change of (110) plane. In addition, this orientation change originated from the self‐induced LC molecule that has a high molecular translational mobility combined with positional and orientational order . The oriented crystallinity and morphology film could impact the electronic properties of perovskite, and it is bound to have further influence on the photovoltaic characteristics of devices.…”
Section: Resultsmentioning
confidence: 99%